TOURISM POTENTIAL OF PODILLIA: CURRENT STATUS AND DEVELOPMENT PROSPECTS (Development Service Industry Management, 2025)
The article examines the tourist potential of Podillya as a unique region of Ukraine with rich natural, historical, cultural and ethnographic resources. It is worth noting that Podillya, due to its geographical location, favorable climatic conditions and rich cultural heritage, has significant tourist potential. This corresponds to the general trends in the development of tourism in Ukraine, where the availability of such resources is considered an important prerequisite for the development of the tourism industry. The article is devoted to a comprehensive analysis of the tourist opportunities of the Podillya region. It should be noted that the authors analyze the current state of the tourist infrastructure of Podillya, including the hotel and restaurant business, transport accessibility and information support. They note both positive aspects and problems that need to be solved to increase the attractiveness of the region for tourists. This trend corresponds to modern methodological approaches to assessing the tourist potential of regions, which provide for a comprehensive analysis of various components. The article also considers the prospects for the development of various types of tourism in Podillya, in particular ecological, cultural and educational, gastronomic, active and health tourism. The authors emphasize the need to introduce new technologies and approaches to increase the competitiveness of the region in the tourism market. Thus, the current state of the tourism infrastructure is analyzed, the main problems are identified and directions for the development of tourism in the region are proposed. In general, the article is a valuable contribution to the study of the tourism potential of Podillya, providing a thorough analysis of the current state and outlining possible ways of developing tourism in the region.
Keywords: Podillya; tourism potential; historical and cultural resources; natural resources; development prospects; tourism infrastructure